Epidemiological and clinical characteristics of Brucella melitensis infections in patients of the Hospital Nacional Daniel A. Carrion, Callao, Peru (2007-2014) - Escobedo M., Lucía (2018)
The objective of this study was to describe the epidemiological and clinical characteristics of human brucellosis in patients with positive diagnosis at the National Hospital «Daniel A. Carrión» (Callao, Peru) in the 2007-2014 period. A total of 68 clinical histories with a positive diagnosis of brucellosis by Brucella melitensis were revised. In 2007, the highest number of cases was recorded (41.1%), and in general, the majority occurred in women (58.8%), from Callao (75.0%), predominantly students (34.5%) and housewives (29.3%). The main clinical signs reported were fever (83.8%), headache (57.4%) and joint pain (55.9%). The most requested laboratory test was Rose Bengal. The results indicate that the disease is present in the environment, so a more efficient control in the animal reservoir is required to prevent the disease in the population.